AN ANALYSIS ON THE ENGLISH TEACHERS’ STRATEGIES IN TEACHING READING COMPREHENSION AT SMP LABSCHOOL PALU - Wahyu Chairun Azis; Jamiluddin Jamiluddin; Anjar Kusumua Dewi (Tadulako University, 2021)
The objectives of this research are (1) to find out the strategies that the English teachers use in teaching reading comprehension at SMP Labschool Palu, (2) to find out the reasons why the English teachers chose the strategies in teaching reading comprehension. The subject of this research all the English teachers at SMP Labschool Palu. This research was descriptive qualitative research. The technique of collecting data were questionnaire and interview. The researcher analyzed the data by using descriptive qualitative research. The result of this research showed that there were five strategies mostly used by the English teachers in teaching reading comprehension to be applied in the classroom. There were (monitoring comprehension, recognizing story structure, question answer relationship, graphic and semantic organizers, and summarizing). Based on the analysis of interview to the teachers, those strategies can help the teachers because the students more active and the students could exchange their opinion with their friends.